Analysis of phenotype array data from Biolog MicroPlates™ - John Bissett; Carol Ann Nolan (浙江大学学报. 农业与生命科学版)
Biolog MicroPlates™ are employed to characterize Trichoderma isolates based on differential assimilation of test substrates and redox reactions in a 96-well test plate. The Biolog method is potentially advantageous in being relatively simple, fast and economical, and data acquisition can be automated using a microplate reader and applicable software. Several research applications of the Biolog system are presented: i) “monophenetic groups” from cluster analyses of phenotype array data are investigated for previously undetected new species in Trichoderma, ii) metabolic characters differentiating species are identified, and multivariate analyses performed to complement molecular data in validating new species and significant variants, and iii) phenotype array data for more than 1200 Trichoderma strains are analysed to select strains that might be exploited for bioconversions and commercial production of enzymes. Phenotype arrays are much more sensitive to strain level variation than molecular techniques, however, phenotype array data do not consistently reflect phylogenies constructed from molecular data. Nevertheless, the Biolog phenotype array is an economical alternative method for surveying biological diversity, and provides data that complements molecular data in phylogenetic studies.